Progressive Dysphasic Dementia with Bucco-Facial Apraxia: A Case Report - S. F. Cappa; C. A. De Fanti; R. De Marco; E. Magni; C. Messa; F. Fazio (Behavioural Neurology)
A patient with progressive dementia, prominent non-fluent aphasia and signs of frontal lobe involvement, was evaluated by neuropsychological testing, magnetic resonance imaging (MRI) and high resolution single photon emission tomography (SPET). The presence of severe bucco-facial apraxia, associated with spared imitation of limb movements, correlated well with a marked reduction of cerebral perfusion in the left fronto-temporal cortex. This case emphasizes the usefulness of SPET as a valuable alternative to PET for the diagnosis of conditions, such as progressive neuropsychological syndromes, where a coupled reduction of metabolism and blood flow can be expected.